THE RELATIONSHIP OF PREGNANCY DISEASE AND LABOR TYPE TO NEONATAL ASPHYXIA AT DR. DRADJAT PRAWIRANEGARA GENERAL HOSPITAL, SERANG IN 2016 - Nila Marwiyah (Faculty of Nursing, Universitas Jember, 2016)
Asphyxia is a condition in which a newborn baby suffers from respiratory failure spontaneously and regularly. It causes neonatal mortality. Globally, 120 million babies are born every year and 1 million of them die because of asphyxia. The research aimed to find the relationship of pregnancy disease and labor type to asphyxia. The research design was cross-sectional. The sample size was 203 babies, taken from secondary data. The statistical test showed that most of the pregnancy disease was severe preeclampsia (45.8%), most of the labor type was spontaneous labor (44.3%), and most of neonatals was moderate asphyxia (82.8%). The result of statistical test by using Chi Square showed p value of 0.025, in which p value < alpha (0.05). It can be concluded that the relationship of pregnancy disease and asphyxia was present. It may happen due to a disease suffered by the mother such as hypertension and preeclampsia which influences placental uterine circulation of fetus. A deficient placental uterine circulation impacts on fetus development disorder and respiratory disorder. Meanwhile, the relationship of labor type and asphyxia showed p value of 0.945. It can be concluded that there was no correlation between labor type and asphyxia. The research recommends monitoring on the condition of pregnant mother and her fetus, especially the mother with pregnancy disease, and motivating pregnant mother to do ANC visits regularly.